Clinical outcomes of endovascular aortic repair in abdominal aortic aneurysms: a single-center experience - Ersoy, Güler Gülsen; Yılmaz, Üzeyir (Journal of Medicine and Palliative Care, 2025)
Aims: This study aims to evaluate the early and mid-term clinical outcomes of 35 patients who underwent endovascular aortic aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) in a tertiary peripheral hospital. Methods: A total of 35 patients who underwent EVAR due to AAA in our hospital between May 2021 and May 2025 were evaluated retrospectively. Demographic characteristics of the patients, aneurysm morphology, intervention details, perioperative complications, postoperative follow-up process, and mortality rates were analyzed. Results: Of the 35 patients included in the study, 30 were male (85.7%) and five were female (14.3%). The mean age was 70.8±7.9 years. The mean aneurysm diameter was measured as 63.1±10.7 mm. Early postoperative mortality was observed in 2 of the patients. Both of these patients were admitted due to ruptured AAA. No other complications were encountered in the early postoperative period. All patients were followed up in the intensive care unit for 24 hours after the procedure. The total hospital stay varied between 5±1 days. Early mortality was observed in 2 patients (5.7%) during the hospital follow-up period. No endoleak was observed in the 6-month follow-up after the procedure. Conclusion: Endovascular aortic aneurysm repair is a safe and effective treatment method with lower morbidity and mortality rates compared to open surgery in appropriate patients. However, regular radiological follow-up of patients and early detection of complications directly affect treatment success.